Modulation of the Aβ-Peptide-Aggregation Pathway by Active Compounds From Platycladus orientalis Seed Extract in Alzheimer’s Disease Models - Yan, Li; He, Xiang; Jin, Yufan; Wang, Jiawei; Liang, Fengying; Pei, Rongrong; Li, Peibo; Wang, Yonggang; Su, Weiwei (Frontiers in Aging Neuroscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by neuronal loss, cognitive impairment and aphasia. Aggregation of β-amyloid (Aβ) peptide in the brain is considered a key mechanism in development of AD. In the past 20 years, many compounds have been developed to inhibit Aβ aggregation and accelerate its degradation. Platycladus orientalis seed is a traditional Chinese medicine used to enhance intelligence and slow aging. We previously found that Platycladus orientalis seed extract (EPOS) inhibited Aβ-peptide aggregation in the hippocampus, and reduced cognitive deficits in 5xFAD mice. However, the mechanisms of these effects have not been characterized. To characterize the protective mechanisms of EPOS, we used a transgenic Caenorhabditis elegans CL4176 model to perform bioactivity-guided identification of active compounds. Four active compounds, comprising communic acid, isocupressic acid, imbricatolic acid, and pinusolide, were identified using 13C‐and 1H‐NMR spectroscopy. Furthermore, we showed that isocupressic acid inhibited Aβ generation by modulating BACE1 activity via the GSK3β/NF-κB pathway in HEK293-APPsw cells. These findings showed that EPOS reduced cognitive deficits in an AD model via modulation of the Aβ peptide aggregation pathway.